ANALYSIS OF LAND SURFACE TEMPERATURE IN THE KRUENG ACEH WATERSHED USING GOOGLE EARTH ENGINE - Khairunnisa, Yulia; Nazhifah, Sri Azizah; Amiren, Muslim; Syahreza, Saumi; Rusdi, Muhammad; Saputra, Kurnia; Putri, Andriani; Sukiakhy, Kikye Martiwi (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2025)
The constantly changing land surface temperature has implications for agricultural productivity and human health, therefore it is important to observe the land surface temperature to provide information about the characteristics and patterns of a region. The purpose of this research is to determine the changes and spatial patterns of land surface temperature distribution in the Krueng Aceh Watershed in 2013, 2018, and 2023. The method employed in this study involves utilizing the Google Earth Engine platform and MODIS imagery. Land surface temperature data from MODIS imagery is processed using JavaScript programming language, and the results are analyzed to obtain the distribution of land surface temperature. The study results indicate that the land surface temperature in the Krueng Aceh Watershed was 29,11℃ in 2013, increase to 29,5℃ in 2018, and then decreased to 29,19℃ in 2023. The Krueng Aceh Watershed in 2013, 2018, and 2023 exhibits similar spatial patterns and distributions of land surface temperature, with areas in Banda Aceh City experiencing higher temperatures compared to those in Aceh Besar District, which exhibit varying temperatures.